ROLE PERCEPTION OF CAREER DEVELOPMENT AND SUPPORT ORGANIZATION TO ORGANIZATION COMMITMENT (RESEARCH NURSE ON HEALTH SERVICES AGENCY REGIONAL HOSPITAL "MARDI WALUYO" BLITAR EAST JAVA) - Mudaim, Mudaim (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2014)
This research was aimed at examining the role of perception of career development and organizational support on the organizational commitment. This study involved seventy nurses of Badan Pelayanan Kesehatan Rumah Sakit Daerah “Mardi Waluyo” Blitar as the subjects of the research. The research data were collected using three scales, that are, scale of perception of career development, organizational support, and organizational commitment.  The hypothesis was that the organizational commitment could be predicted from the perception of career development and organizational support. The data were analyzed with multivariate regression analysis.The results of this research showed that perception of career development and organizational support had very significant role on organizational commitment (F: 6.589; R2 = 0.164; p = 0.003), beside that, perception of career development had very significant with organizational commitment (F = 12.922; r = 0.161; p = 0.001), but the organizational support with organizational commitment was insignificant (F = 0.257; r = 0.003; p = 0.620).Keywords: organizational commitment, career development, organizational support.